DIVERSE INTERACTIONS OF RETROVIRAL GAG PROTEINS WITH RNAs - Rein, Alan (2011)
Retrovirus particles are constructed from a single virus-encoded protein, termed Gag. Given that assembly is an essential step in the viral replication cycle, it is a potential target for antiviral therapy. However, such an approach has not yet been exploited because of the lack of fundamental knowledge concerning the structures and interactions responsible for assembly. Assembling an infectious particle entails a remarkably diverse array of interactions, both specific and nonspecific, between Gag proteins and RNAs.These interactions are essential for the construction of the particle, for packaging the viral RNA into the particle, and for placement of the primer for viral DNA synthesis. Recent results have provided some new insights into each of these interactions. In the case of HIV-1 Gag, it is clear that more than one domain of the protein contributes to Gag-RNA interaction.